Low-Vision Evaluations and Interventions Used in Practice. Issue 3 (July 2022) - Nastasi, Julie Ann; Blasland, Rachel; Desseyn, Danielle; Gaynor, Samantha; Grieco, Alexa; Kelly, Emily; McMullen, Brigid; Rice, Lauren; Strassle, Brianna
Abstract : Low vision creates challenges in completing vision-dependent tasks and activities. The purpose of this 3-round e-Delphi study was to determine a consensus for the evaluations and interventions commonly used in low-vision rehabilitation for older adults with low vision. Ten occupational therapists with at least 3 years of practice in low-vision rehabilitation participated in the study. The results of the study identified the most frequently used evaluations and interventions for older adults with low vision. Findings of this study coincided with the literature and can be integrated into current practice with this population.